High Income Protects Whites but Not African Americans against Risk of Depression - Assari, Shervin (Healthcare (Basel), 2018)
Background: Built on the Blacks’ diminished return theory, defined as smaller effects of socioeconomic status (SES) on a wide range of health outcomes for African Americans compared to Whites, the current study compared African Americans and Whites for the association between household income and risk of lifetime, 12-month, and 30-day major depressive disorder (MDD). Methods: For the current cross-sectional study, we used data from the Collaborative Psychiatric Epidemiology Surveys (CPES), 2001–2003. With a nationally representative sampling, CPES included 4746 non-Hispanic African Americans and 7587 non-Hispanic Whites. The dependent variables were lifetime, 12-month, and 30-day MDD, measured using Composite International Diagnostic Interview (CIDI). The independent variable was household income. Age, gender, education, chronic medical conditions, and obesity were covariates. Race was the focal moderator. Logistic regression models were used to test the protective effects of household income against MDD in the overall sample and also by race. Results: In the overall sample, household income was inversely associated with the risk of 12-month and 30-day MDD. We found a significant interaction between race and household income on 12-month and 30-day MDD, suggesting a smaller protective effect of household income against MDD for African Americans compared to Whites. Conclusion: In line with the Blacks’ diminished return theory, household income better protects Whites than African Americans against MDD. The contribution of diminished return of SES as an underlying mechanism behind racial disparities in health in the United States is often overlooked. Additional research is needed on why and how SES resources generate smaller health gain among minority groups.